Evaluasi Pelaksanaan Program Bantuan Pangan Non Tunai Di Kota Batam - Tan, Tri Juniati; Epriadi, Dedi (SCIENTIA JOURNAL, 2021)
Non Cash Food Aid in the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 20 of 2019 concerning the Distribution of Non Cash Food Aid is social assistance that is distributed non-cash from the government which is given to Beneficiary Familie every month through electronic money then used for buy foodstuffs that have been determined at the e-warong. Through this research, the authors aim to find out how the implementation of the non cash food aid program in Batam City and determine the factors that hinder the implementation of non cash food aid in Batam City. The research was conducted using a qualitative method with a descriptive approach and the data source of this research consists of primary data and secondary data. The results of this study indicate all parties involved in this program implementing the Non Cash Food Aid Program (BPNT) is guided by the Regulation concerning the Distribution of Non Cash Food Aid. The factors that hinder the implementation of the Non Cash Food Aid Program in Batam City in 2020 are the lack of cooperation from various parties, the lack of clarity on applicable regulations, and the lack of public awareness in maintaining the media properly.